2023
DOI: 10.1111/1471-0307.12923
|View full text |Cite
|
Sign up to set email alerts
|

The migration and degradation of N‐(1,3‐dimethylbutyl)‐N′‐phenyl‐p‐phenylenediamine from rubber hoses in milk lines

Abstract: N‐(1,3‐dimethylbutyl)‐N′‐phenyl‐p‐phenylenediamine (6PPD), an anti‐ageing agent in rubber hoses used in milk lines, may migrate into the milk and cause safety issues. Thus its migration and degradation in simulants/milk were studied to explore the changing trends and final levels, by high‐performance liquid chromatography. The results showed that 6PPD continuously increased in 95% ethanol and degraded more easily in simulants with a high water content. The degradation may be attributed to the π‐conjugated syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Rubber hoses in contact with food are commonly utilized in large-scale dairies to transport milk. 6PPD is an antiaging agent for rubber articles intended for repeated food-contact use . However, a study investigating milk lines confirmed that milk safety and quality were not affected by 6PPD migration and degradation …”
Section: Ppdq In the Environmentmentioning
confidence: 99%
“…Rubber hoses in contact with food are commonly utilized in large-scale dairies to transport milk. 6PPD is an antiaging agent for rubber articles intended for repeated food-contact use . However, a study investigating milk lines confirmed that milk safety and quality were not affected by 6PPD migration and degradation …”
Section: Ppdq In the Environmentmentioning
confidence: 99%